Chemical structures, biological activities, and medicinal potentials of amine compounds detected from Aloe species - Yadeta, Adamu Tizazu (Frontiers in Chemistry, 2024)
Unrestricted interest in Aloe species has grown rapidly, and a lot of research is currently being done to learn more about the properties of the various Aloe constituents. Organic compounds containing amine as functional group are present in a vivid variety of compounds, namely, amino acids, hormones, neurotransmitters, DNA, alkaloids, dyes, etc. These compounds have amine functional groups that have various biological activities, which make them responsible for medicinal potential in the form of pharmaceutical, nutraceutical, and cosmeceutical applications. Consequently, the present review work provides an indication of the amines investigated in Aloe species and their therapeutic uses. Various amine compounds of the Aloe species have effective biological properties to treat diseases. Generally, the genus Aloe has various active amine-containing compounds to combat diseases when humans use them in various forms.